POLA REKRUTMEN CALON LEGISLATIF PROVINSI JAWA TENGAH PARTAI NASIONAL DEMOKRAT PADA PEMILU 2014 (STUDI DI DPW PARTAI NASIONAL DEMOKRAT JAWA TENGAH) - Arinta Yulysa Purwitasari; Rina Martini; Nunik Retno H (Journal of Politic and Government Studies, 2015)
Political parties and parliament (legislature) are the two main factors of political society, which is a mandate from civil society with a role in organizing power and gained control over the country in the interests of society. NasDem party as a relatively new party, the election agenda is part of implementation of commitments in the restoration and alteration. In 2014 elections, NasDem party have targets to win the legislative elections. One of the winning strategy is to recruit one character that has the capacity, integrity, popularity and the same ideology as NasDem party.The purpose of this study was to determine what kind of recruitment patterns that NasDem party do against its legislative candidates, and to determine the factors that influence the recruitment of candidates on NasDem party.The research method used is qualitative research to explore in depth information. This research aims to determine strategies of NasDem party in determining legislative candidates who will occupy Central Java Provincial Parliament (DPRD Provinsi Jawa Tengah). Spesification of this research is descriptive analytical.sOf the results obtained, indicate that : 1) the pattern of recruitment is done by DPD NasDem party of Central Java using the Merit System. 2) there are two factors that influence the recruitment patterns of NasDem party, namely internal and eksternal factors. Internal factors include systemic dimension, where the system and structural building NasDem party itself has a great influence in attracting the party membership and recruitment of legislative candidates. Reification demension is about the image and political assessment of NasDem party. The next external factor is a factor that comes from the prospective member of legislative candidates regarding the qualifications and personality of each prospective member of the legislature itself.Conclusions of this study is DPD Nasdem party has done with recruitment process as appropriate in accordance special prevailing party lines and other common applicable regulatory pathways.